FAKTOR-FAKTOR YANG MEMPENGARUHI ANGGOTA DALAM MEMILIH JASA SIMPANAN TAHUN 2019 STUDI KASUS DI BMT TUMANG CABANG CEPOGO - melia rifa afina; dasmadi dasmadi; A Fidhdiarr (Universitas Boyolali, 2019)
The purpose of this study was to analyze the influence of sharia factors, promotion and product quality on member decisions in choosing savings services at BMT Tumang Cepogo Branch. This type of research based on its approach is quantitative research. This study uses a correlational design that is the relationship between the independent variables X1, X2 and X3 to the dependent variable Y. The population of this study is all members of the BMT Tumang Cepogo Branch. The sampling technique in this research is accidental sampling. The number of samples taken in this study were 100 respondents. This study uses a multiple linear regression data analysis approach. Based on the research results it is known that sharia factors, promotion and product quality partially and simultaneously significantly influence the decision of members in choosing savings services, this is because BMT Tumang Cepogo Branch sees a factor that can increase members' decision in choosing savings services, including due to sharia factors , promotion and product quality, so that many members choose savings services at BMT Tumang Cepogo Branch due to sharia factors, promotion intensity and product quality. Keywords: sharia factor, promotion, product quality, deposit services